Tinjauan Kritis terhadap Asas Droit De Suite pada Jaminan Hak Tanggungan dalam Konteks Perlindungan Pembeli yang Beriktikad Baik - Emmi Rahmiwita Nasution; Dormada Lestari Luhur Sitorus (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to analyze the legal conflict between the principle of droit de suite in mortgage rights and legal protection for land buyers in good faith. Using normative juridical research methods, this study examines the implementation of Law Number 4 of 1996 concerning Mortgage Rights (UUHT). The research findings indicate that the absolute application of the principle of droit de suite provides a privileged position for creditors, but often sacrifices honest buyers due to their ignorance of the collateral status of the sale and purchase object. A normative imbalance occurs where legal certainty in the banking business is prioritized over the public sense of justice. Therefore, regulatory reforms are needed that limit the absolute execution rights of creditors when dealing with buyers in good faith who have conducted due diligence, as well as the need to increase data transparency in the land administration system.